Digital Learning Innovation: Gamification-Based Smart System Adaptive Mobile Learning Needs Analysis Using the Tri Kaya Parisudha Approach for English Language Learning - Jayanta, I Nyoman Laba; Suprianti, G.A.P.; Ganing, Ni Nyoman; Utami, I GA Lokita Purnamika (Universitas Negeri Makassar, 2025)
Many elementary school students do not enjoy learning English due to ineffective instructional approaches that limit independent learning. While digital technology offers potential solutions, its educational use faces challenges such as misinformation and students’ low digital resilience. This study investigates the current levels of digital innovation and digital resilience among elementary students and explores strategies to enhance these skills. A concurrent embedded mixed-methods design was used, involving 120 fifth-grade students and teachers from elementary schools across Bali, selected through purposive sampling. Data were collected using questionnaires and analyzed both quantitatively and qualitatively. Results show that students’ innovation and resilience in digital contexts remain low, and existing learning activities have not significantly improved these competencies. However, teachers support efforts to foster these skills. To address this gap, the study proposes the development of a Smart System Adaptive Mobile Learning (SSAML) system that incorporates gamification and the Tri Kaya Parisudha philosophy—a Balinese framework emphasizing good thoughts, speech, and actions. This culturally grounded digital learning model is intended to provide effective feedback, enhance student motivation, and promote digital innovation and resilience in English language learning.